Antibacterial quaternary ammonium compounds in dental materials: A systematic review. Issue 6 (June 2018) - Makvandi, Pooyan; Jamaledin, Rezvan; Jabbari, Mostafa; Nikfarjam, Nasser; Borzacchiello, Assunta
Abstract: Objective: Quaternary ammonium compounds (QACs) represent one of the most effective classes of disinfectant agents in dental materials and resin nanocomposites. This reviews aims to give a wide overview on the research in the field of antibacterial QACs in dental materials and nanocomposites. Method: An introduction to dental materials components as well as the microorganisms and methods of evaluation for the antimicrobial assays are presented. Then, the properties and synthesis route of QACs, as monomer and filler, are shown. Finally, antimicrobial monomers and fillers, specifically those contain quaternary ammonium salts (QASs), in dental materials are reviewed. Results: QACs have been used as monomer and micro/nanofiller in restorative dentistry. They possess one or more methacrylate functional groups to participate in polymerization reactions. QACs with multiple methacrylate groups can also be used as crosslinking agents. Furthermore, QACs with chain length from ∼12 to 16 have higher antimicrobial activity in cured dental resins. In general, increasing the chain length leads to a threshold value (critical point) and then it causes decrease in the antimicrobial activity. Significance: The current state of the art of dental materials and resin nanocomposites includes a wide variety of antimicrobial materials. Among them, QACs presents low cytotoxicity and excellent long-term antimicrobial activity without leaching out over time.